Modifikasi Tanda Tangan Digital Pada Skema Esign Berbasis Kurva Eliptik - Sa'aadah Sajjana Carita; Evie Sri Wahyuni (STMIK Sinar Nusantara, 2022)
Digital signature has an important role in the digital era, where more and more people are joining the paperless life. Many cryptographic researchers support digital development by creating cryptographic schemes that are safe to use, and one of them is digital signature. This paper proposes a digital signature scheme based on an elliptic curve defined over with , where and are private keys of prime number elements. This scheme utilizes the advantages of elliptic curve cryptography in terms of security by using points that satisfy the elliptic curve equation. Additionally, the shorter key size increases the speed, making this scheme faster in signature values generation and verification process.This research was conducted to determine the differences between the modified ESIGN scheme based on elliptic curve and the original ESIGN scheme. The process of finding the point on the ring , with a large , resulted in a more complex key generation algorithm. However, the selection of two points in this key generation is precomputed. This means the actual signature value generation algorithm took significantly less time than the original. This is one of the advantages of the proposed scheme.